A Data-driven Modeling Approach to Stochastic Computation for Low-energy Biomedical Devices - Lee, Kyong-Ho; Jang, Kuk; Zarar, Shuayb; Shoeb, Ali; Verma, Naveen (IEEE/ACM Design Automation Conference (DAC), 2011)
Data-driven modeling is a powerful way to handle errors in hardware by taking advantage of machine learning algorithms. We propose a error-aware models that handle high rate of errors in arrhythmia and seizure detection applications with nearly no extra cost in hardware.
Design Automation Conference (DAC)